Предмет: Математика,
автор: Глинка
решить двумя способами:
а) ( x+39)-43=27
б)(60-x)-16=20
Ответы
Автор ответа:
0
а) ( x+39)-43=27 ( x+39)-43=27
x-39-43=27 x-39-43=27
x=27+39+43 x-82=27
x=109 x=27+82
x=109
б)(60-x)-16=20 (60-x)-16=20
60+x-16=20 60+x-16=20
x=20-60+16 44+x=20
x=-24 x=20-44
x=-24
x-39-43=27 x-39-43=27
x=27+39+43 x-82=27
x=109 x=27+82
x=109
б)(60-x)-16=20 (60-x)-16=20
60+x-16=20 60+x-16=20
x=20-60+16 44+x=20
x=-24 x=20-44
x=-24
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Українська література,
автор: olegoleksivich
Предмет: Алгебра,
автор: uliashka45
Предмет: Информатика,
автор: svetlanabelova